2022
DOI: 10.1101/2022.11.15.516559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TORC1 regulation of dendrite regrowth after pruning is linked to actin and exocytosis

Abstract: Neurite pruning and regrowth are important mechanisms to adapt neural circuits to distinct developmental stages. Neurite regrowth after pruning often depends on differential regulation of growth signaling pathways, but their precise mechanisms of action during regrowth are unclear. Here, we show that the PI3K/TORC1 pathway is required for dendrite regrowth after pruning in Drosophila peripheral neurons during metamorphosis. TORC1 impinges on translation initiation, and our analysis of 5' untranslated regions (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Owing to the difficulty of experimental manipulation during this stage, the specific mechanisms underlying the regrowth process after dendrite pruning are just starting to be appreciated. A recent study from Rumpf’s lab has suggested that the PI3K/TORC1 pathway orchestrates the regrowth of pruned dendrites by coordinating the activation of protein biosynthesis of regrowth factors including the actin cytoskeleton and exocytosis [67]. Noteworthily, previous studies have also revealed an important role for actin dynamic as well as exocytosis-associated protein secretion process in dendritic pruning [40,50,52,53], suggesting that pruning and regrow share similar regulatory mechanisms.…”
Section: The Pi3k/torc1 Pathway In the Regrowth After Dendrite Pruningmentioning
confidence: 99%
“…Owing to the difficulty of experimental manipulation during this stage, the specific mechanisms underlying the regrowth process after dendrite pruning are just starting to be appreciated. A recent study from Rumpf’s lab has suggested that the PI3K/TORC1 pathway orchestrates the regrowth of pruned dendrites by coordinating the activation of protein biosynthesis of regrowth factors including the actin cytoskeleton and exocytosis [67]. Noteworthily, previous studies have also revealed an important role for actin dynamic as well as exocytosis-associated protein secretion process in dendritic pruning [40,50,52,53], suggesting that pruning and regrow share similar regulatory mechanisms.…”
Section: The Pi3k/torc1 Pathway In the Regrowth After Dendrite Pruningmentioning
confidence: 99%
“…AMPK also counteracts the Target of rapamycin Complex 1 (TORC1) kinase during c4da neuron dendrite pruning, a known activator of mRNA translation [ 33 ]. It is interesting to speculate that TORC1 inhibition saves energy, but negative regulation of TORC1 is likely also a regulatory mechanism during development because it is reactivated after pruning to promote regrowth of adult-adapted sensory dendrites [ 41 ]. TORC1 inhibition is also required for macroautophagy during postsynaptic pruning in mouse cortical neurons [ 42 ], suggesting at least partial conservation of metabolic control during pruning.…”
Section: Metabolic Regulation During Neuronal Differentiation and Mor...mentioning
confidence: 99%